2001
DOI: 10.1017/s1049096501000154
|View full text |Cite
|
Sign up to set email alerts
|

Minority Mayors and the Hollow-Prize Problem

Abstract: The number of African American and Hispanic mayors of American cities has grown steadily since 1967, the year that Cleveland elected Carl Stokes the first minority mayor of a major American city.Throughout this paper, we use the term “minority” to refer to African Americans and Hispanics. In doing so, we do not assume that African American and Hispanic voters have the same preferences, nor do we intend to minimize the significant diversity within each of these groups. Rather, we group Hispanics and African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…Gilliam and Kaufman (1998, 743), for instance, indicate that symbolic benefits may come bundled with enhanced expectations of policy responsiveness from black administrations. The danger inherent in lofty expectations may explain the failure of black political leaders to meet these expectations, a shortfall often referred to as the “hollow hope” (see, e.g., Kraus and Swanstrom 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gilliam and Kaufman (1998, 743), for instance, indicate that symbolic benefits may come bundled with enhanced expectations of policy responsiveness from black administrations. The danger inherent in lofty expectations may explain the failure of black political leaders to meet these expectations, a shortfall often referred to as the “hollow hope” (see, e.g., Kraus and Swanstrom 2001).…”
Section: Discussionmentioning
confidence: 99%
“…And they must do so as deindustrialization and suburbanization erode their economic base (Rae, 2003;Sugrue, 1996;Wilson, 1996). Past scholarship has also suggested that these fiscal and economic constraints are especially binding in the cities that tend to elect black mayors (Friesema, 1969;Howard, 1978;Kraus & Swanstrom, 2001;Nelson, 1978). Irrespective of their preferences, the hypothesis that emerges is one of mayors unable to challenge status quo policies.…”
Section: Mayors' Limitsmentioning
confidence: 99%
“…And they must do so as deindustrialization and suburbanization erode their economic base (Sugrue, 1996;Wilson, 1996;Rae, 2003). Past scholarship has also suggested that these fiscal and economic constraints are especially binding in the cities that tend to elect black mayors (Friesema, 1969;Howard, 1978;Nelson, 1978;Kraus and Swanstrom, 2001). Irrespective of their preferences, the hypothesis that emerges is one of mayors unable to challenge status quo policies.…”
Section: Mayors' Limitsmentioning
confidence: 99%
“…Whether the answer is yes or no, it will challenge at least one prominent theoretical approach to urban politics. Not long after the election of the first black, big-city mayors in 1967, observers began to question whether control over cities was a "hollow prize" given their fiscal and economic dependence (Friesema, 1969;Kraus and Swanstrom, 2001;Self, 2003). Building from Peterson's 1981 claim that city policy is sharply constrained by economic competition, this research tradition emphasizes the external limitations on autonomous urban policymaking (e.g.…”
Section: Introductionmentioning
confidence: 99%